The Work Productivity of Employees Perspective By Work Discipline And Work Environment - Irwansyah, Kiki Hidayat; Nuralifah, Rika; Maryati, Sri; Nurdiana, Editya (IJBLE Scientific Publications Community Inc., 2024)
The purpose of this study is to examine how PT staff' work environments and work discipline affect their productivity. Margarita Works. Quantitative approaches are employed in this study. using methods for gathering data such as interviews and questionnaires. The study included 61 workers from PT Jasa Marga Palikanci as respondents. Multiple linear regression is the analytical technique employed, and the regression coefficient values are Y = 0.516 + 0.171 X1 + 0.137 X2. The research hypothesis test results indicate that PT employees' job productivity is influenced by work environment and work discipline. Jasa Marga, either in part or entirely at once